Improved Control Strategy of the Modular Multilevel Converter for High Power Drive Applications in Low Frequency Operation - Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2016)
Modular Multilevel Converters (M2C) are considered an attractive solution for high power drives. However, its operation at low rotational speeds can produce undesired voltage fluctuations in the M2C capacitors. In this paper, two methodologies to improve the converter performance in this speed range are analysed and tested. The first strategy proposes the control of the inner converter currents combining a synchronous dq rotating frame and resonant controllers to improve the current tracking and to reduce the voltage fluctuations. The second strategy achieves the reduction of the voltage fluctuations by adjusting the DC Port voltage as a function of the machine frequency. Both methods are validated by simulation and experimental work, where a 18 cell M2C prototype is applied to drive an induction machine. © 2016 IEEE and EPE Association.